COMBUSTION OF DEWATERED POULTRY SLUDGE IN A LABORATORY SCALE FLUIDIZED BED COMBUSTOR - ABBAS ATYA, ABBAS HASSAN (2015)
Dewatered sludge is considered as one of the largest contributors of biomass waste material in Malaysia. The disposal of this waste through landfilling method is an expensive process and if not handled according to the stringent procedures, can be harmful to the environment The use of this waste material as an alternative fuel source can mitigate environmental issues related to its disposaL Combustion is considered as one of the etT'icient techniques of utilizing energy from biomass waste. However, studies on thermochemical conversion of poultry sludge are extremelv scarce, and no research has been documented on experimental level and modeling of poultrx sludge combustion. The main objective of th1s research is to mvestigate the performance of poultry sludge as a source of solid fuel. The combustion characteristics of poultry sludge such as the amount of moisture content, energy content, proximate analyses and ultimate analyses were investigated prior to the combustion experiments.